Commensal Lactobacilli Enhance Sperm Qualitative Parameters in Dogs - Mahiddine, Feriel Yasmine; You, Inhwan; Park, Heekee; Kim, Min Jung (Frontiers in Veterinary Science, 2022)
Although several methods have been developed to improve male fertility and sperm quality, subfertility remains a primary clinical issue in male reproduction worldwide. The aim of this study was to determine the effects of the oral administration of three commensal Lactobacillus spp. on healthy normozoospermic dogs and the qualitative parameters of their sperm. Three weeks of supplementation induced a significant decrease of two phyla, Proteobacteria and Tenericutes, and an increase of phylum Firmicutes. At the species level, the number of Fusobacterium perfoetens and Anaerobiospirillum succiniciproducens decreased, while Limosilactobacillus reuteri increased. Parallel to these results, qualitative sperm parameters such as total and progressive motility, acrosome integrity, and other kinematic parameters were significantly enhanced after commensal lactobacilli supplementation. In addition, we showed that Firmicutes were positively correlated with sperm qualitative parameters, while Proteobacteria, F. perfoetens, and A. succiniciproducens were negatively correlated. Considering the similarities between dogs and the human gut microbiome, these results provide more insight into how gut microbiota regulation could improve male sperm quality in both species.